2023
DOI: 10.2147/opth.s405837
|View full text |Cite
|
Sign up to set email alerts
|

Trabeculectomy Vs Non‐penetrating Deep Sclerectomy for the Surgical Treatment of Open-Angle Glaucoma: A Long-Term Report of 201 Eyes

Abstract: Introduction Glaucoma is the second leading cause of vision loss worldwide. The reduction of intraocular pressure remains the backbone of its therapy. Among surgical techniques for its treatment, deep non-penetrating sclerotomy is the most widely practiced non-penetrating surgery. The purpose of this study was to evaluate the long-term efficacy and safety of deep non-penetrating sclerotomy compared to standard trabeculectomy in patients with open-angle glaucoma. Patients and methods… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 21 publications
0
1
0
Order By: Relevance
“…In contrast, Chiselita reported a lower IOP after trabeculectomy than after NPDS, with a lower complication rate in the latter, in adults with primary open-angle glaucoma [ 36 ]. Correia Barbosa et al reached a similar conclusion in a group of adults with open-angle glaucoma [ 37 ]. This observed difference may indicate variable efficacy of the NPDS for different age groups.…”
Section: Discussionmentioning
confidence: 58%
“…In contrast, Chiselita reported a lower IOP after trabeculectomy than after NPDS, with a lower complication rate in the latter, in adults with primary open-angle glaucoma [ 36 ]. Correia Barbosa et al reached a similar conclusion in a group of adults with open-angle glaucoma [ 37 ]. This observed difference may indicate variable efficacy of the NPDS for different age groups.…”
Section: Discussionmentioning
confidence: 58%
“…ElSayyad et al reported that some aqueous humor enters the suprachoroidal space, passes through the subconjunctival pathway, and reaches the filtration bleb [ 34 ]. A scleral flap can help regulate the aqueous outflow by providing resistance [ 35 ]. Episcleral venous drainage, conjunctival bleb, scleral channels, and suprachoroidal filtration are potential mechanisms for lowering IOP.…”
Section: Discussionmentioning
confidence: 99%